2020
DOI: 10.1177/2040622320944773
|View full text |Cite
|
Sign up to set email alerts
|

Teriflunomide preserves peripheral nerve mitochondria from oxidative stress-mediated alterations

Abstract: Mitochondrial dysfunction is a common pathological hallmark in various inflammatory and degenerative diseases of the central nervous system, including multiple sclerosis (MS). We previously showed that oxidative stress alters axonal mitochondria, limiting their transport and inducing conformational changes that lead to axonal damage. Teriflunomide (TFN), an oral immunomodulatory drug approved for the treatment of relapsing forms of MS, reversibly inhibits dihydroorotate dehydrogenase (DHODH). DHODH is crucial … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
12
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 61 publications
(106 reference statements)
7
12
1
1
Order By: Relevance
“…In this context, we have investigated the therapeutic potential of the DHODH inhibitor TFN, an approved drug for the treatment of RRMS [19,20], on both neuronal and mitochondrial protection. Using a model in peripheral root explants, we have previously shown that mitochondria become shorter and rounder, and were less motile, during oxidative stress [28,30]. Importantly, using this model of peripheral nerves, we recently demonstrated that TFN could prevent the morphologic alterations of axonal mitochondria caused by oxidative stress [28].…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…In this context, we have investigated the therapeutic potential of the DHODH inhibitor TFN, an approved drug for the treatment of RRMS [19,20], on both neuronal and mitochondrial protection. Using a model in peripheral root explants, we have previously shown that mitochondria become shorter and rounder, and were less motile, during oxidative stress [28,30]. Importantly, using this model of peripheral nerves, we recently demonstrated that TFN could prevent the morphologic alterations of axonal mitochondria caused by oxidative stress [28].…”
Section: Discussionmentioning
confidence: 92%
“…We have shown previously that in peripheral nerves, mitochondria exposed to oxidative stress are affected even prior to the axonal damages [28,30] and that TFN prevents these mitochondrial alterations [28]. To monitor how TFN affects changes of mitochondria morphology during oxidative stress within the CNS, hippocampal slices from transgenic Tg(Thy1-CFP/COX8A)S2Lich/J mice (mitoCFP mice) that express cyan fluorescence protein (CFP) in neuronal mitochondria were imaged before (baseline image) and after the treatment with H 2 O 2 or H 2 O 2 + TFN.…”
Section: Tfn Prevented Oxidative Stress-induced Decrease In Mitochond...mentioning
confidence: 97%
See 2 more Smart Citations
“…However, there were no symptoms of oxidative stress in teriflunomide treated cells. Despite this fact, there have been several reports of oxidative stress reduction—e.g., in fetal human pulmonary arterial endothelial cells due teriflunomide treatment [ 34 ]—and its ability to preserve peripheral nerve mitochondria from oxidative stress [ 35 ].…”
Section: Discussionmentioning
confidence: 99%